Positive electrode active material for all-solid-state lithium ion secondary battery, and all-solid-state lithium ion secondary battery
Patent Information
- Application Number
- JP2023132647
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-28
AI Technical Summary
【0018】 本発明によれば、被覆層を有する全固体リチウムイオン二次電池用正極活物質として、より高い放電容量を有する正極活物質を提供することができる。
Smart Images

Figure 2025027661000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for an all-solid-state lithium ion secondary battery and an all-solid-state lithium ion secondary battery. [Background technology]
[0002] In recent years, with the spread of electric vehicles, there is a strong demand for the development of small, lightweight secondary batteries with high energy density. One such secondary battery is a lithium-ion secondary battery. The lithium-ion secondary battery includes a positive electrode, a negative electrode, and an electrolyte. The active materials used for the negative electrode and the positive electrode are materials capable of desorbing and inserting lithium.
[0003] Currently, typical lithium-ion secondary batteries use lithium transition metal composite oxides such as LiCoO2, LiNiO2, and LiMn2O4 as the positive electrode active material, lithium metal, lithium alloys, metal oxides, carbon, etc. as the negative electrode active material, and an electrolyte solution made by dissolving a Li salt such as LiClO4 or LiPF6 as a supporting salt in an organic solvent such as ethylene carbonate, dimethyl carbonate, or ethyl methyl carbonate is used.
[0004] Among the components of the lithium-ion secondary battery, the electrolyte in particular is a factor that limits the battery's performance, such as high-speed charging, safety, and lifespan, due to its chemical properties such as heat resistance and potential window. Therefore, research and development is currently being actively conducted on all-solid-state lithium-ion secondary batteries (hereinafter simply referred to as "all-solid-state batteries") that improve battery performance by using a solid electrolyte instead of an electrolyte.
[0005] In the course of research and development, for example, Patent Document 1 proposes that, among solid electrolytes, sulfide-based solid electrolytes have high lithium ion conductivity and are preferable for use in all-solid-state batteries. However, as disclosed in Non-Patent Document 1, when a sulfide-based solid electrolyte comes into contact with a positive electrode active material that is an oxide, a reaction occurs at the contact interface between the solid electrolyte and the positive electrode active material during charging and discharging, and a high-resistance layer is formed at the interface, inhibiting the operation of the battery.
[0006] For example, Patent Document 2 proposes providing a lithium ion conductive oxide coating layer on the surface of the positive electrode active material in order to suppress the formation of this high resistance layer. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2014-056661 A [Patent Document 2] International Publication No. 2007 / 004590 [Non-patent literature]
[0008] [Non-Patent Document 1] Narumi Ohta et al., “LiNbO3-coated LiCoO2 as cathode material for all solid-state lithium secondary batteries”, Electrochemistry Communications 9 (2007) 1486-1490 Summary of the Invention [Problem to be solved by the invention]
[0009] For example, in the examples of Patent Document 2, it is disclosed that the formation of a high resistance layer can be suppressed by providing a coating layer made of LiNbO3, which is one of lithium ion conductive oxides, on the surface of the positive electrode active material, thereby enabling the discharge capacity of the all-solid-state battery to be increased. However, the charge / discharge capacity is still low compared to a lithium ion secondary battery that uses an electrolytic solution as the electrolyte, and a further increase in the charge / discharge capacity is desired.
[0010] In view of the above problems, an object of the present invention is to provide a positive electrode active material having a coating layer and a higher discharge capacity as a positive electrode active material for an all-solid-state lithium ion secondary battery. [Means for solving the problem]
[0011] In order to solve the above problems, the present inventors conducted extensive research into a positive electrode active material for an all-solid-state battery having a coating layer that suppresses interfacial reactions with a solid electrolyte and a positive electrode active material, and found that the charge / discharge capacity of an all-solid-state battery can be increased by coating the secondary particle surface of the positive electrode active material with a compound consisting of at least lithium and tungsten in a specific ratio.
[0012] In a first aspect of the present invention, there is provided a positive electrode active material for an all-solid-state lithium ion secondary battery, the positive electrode active material having a lithium transition metal composite oxide composed of secondary particles formed by aggregation of a plurality of primary particles, and a coating layer coating the surfaces of the secondary particles, in which the lithium transition metal composite oxide contains lithium, nickel, and optionally cobalt, and an element M (wherein the element M is an added element other than lithium, nickel, cobalt, and oxygen), the coating layer contains a compound containing at least lithium and tungsten, and the coverage of tungsten on the surfaces of the secondary particles P (%) calculated by the following (Equation 1) is 30% or more and 95% or less.
[0013] P=(W / (W+Ni+Co+M))×100(%) …(Formula 1) W: The amount of tungsten determined by X-ray photoelectron spectroscopy (XPS analysis) Ni: The amount of nickel determined by X-ray photoelectron spectroscopy (XPS analysis) Co: Amount of cobalt determined by X-ray photoelectron spectroscopy (XPS analysis) M: The amount of element M (excluding tungsten) quantified by X-ray photoelectron spectroscopy (XPS analysis)
[0014] The lithium transition metal composite oxide is preferably represented by the following formula (2).
[0015] Li a Ni 1-x-y Co x M y O 2+z …(Formula 2) Here, M is one or more elements selected from Mg, Ca, Sr, Ba, Al, Ti, V, Cr, Mn, Fe, Cu, Zr, Nb, Mo, W, Ta, Si, P, and B, and satisfies 0.9≦a≦1.2, 0.01≦x≦0.5, 0.01≦y≦0.5, 0.02≦x+y<1.0, -0.1≦z≦0.1.
[0016] In addition, it is preferable that the lithium transition metal composite oxide has a compound containing tungsten present between the primary particles inside the secondary particles. It is preferable that the coverage P is 60% or more and 95% or less. It is preferable that the coverage P is 80% or more and 95% or less. It is preferable that the lithium transition metal composite oxide has a volume average particle diameter Mv of 1 μm or more and 10 μm or less. It is preferable that the content of tungsten contained in the positive electrode active material is 0.1 mass % or more and 6 mass % or less with respect to the total amount of the positive electrode active material. It is preferable that the pore volume of the positive electrode active material is 0.001 cm 3 / g or more 0.008cm 3 / g or less, and the average pore size of the positive electrode active material is preferably 1 nm or more and 10 nm or less.
[0017] In a second aspect of the present invention, there is provided an all-solid-state lithium-ion secondary battery comprising a positive electrode, a negative electrode, and a solid electrolyte, each containing the above-mentioned positive electrode active material for an all-solid-state lithium-ion secondary battery. Effect of the Invention
[0018] According to the present invention, it is possible to provide a positive electrode active material having a higher discharge capacity as a positive electrode active material for an all-solid-state lithium ion secondary battery having a coating layer. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic diagram showing an example of the positive electrode active material according to this embodiment. [Diagram 2] FIG. 2 is an explanatory diagram of a cross-sectional configuration of an evaluation battery used in battery evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, in order to make each configuration easier to understand, some parts are emphasized or simplified, and the actual structure, shape, scale, etc. may differ. In addition, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment without departing from the scope of the present invention.
[0021] 1. Positive electrode active material for all-solid-state lithium-ion secondary batteries An example of the configuration of the positive electrode active material for an all-solid-state lithium ion secondary battery according to this embodiment (hereinafter, also simply referred to as the "positive electrode active material") will be described.
[0022] Fig. 1 is a diagram showing a schematic diagram of an example of a positive electrode active material according to the present embodiment. As shown in Fig. 1, a positive electrode active material 10 has a lithium transition metal composite oxide 1 and a coating layer 2 that coats the surface of the lithium transition metal composite oxide 1. Each component will be described below.
[0023] (1) Lithium transition metal composite oxide The lithium transition metal composite oxide 1 is composed of secondary particles formed by aggregation of a plurality of primary particles. The lithium transition metal composite oxide 1 may contain lithium, a transition metal, and oxygen, and may have a layered rock salt type crystal structure.
[0024] (composition) The lithium transition metal composite oxide 1 is a compound containing lithium, a transition metal, and oxygen, and preferably contains nickel as the transition metal, and more preferably contains nickel and cobalt. The lithium transition metal composite oxide 1 preferably has a composition represented by the following general formula (1), for example.
[0025] General formula (1): Li a Ni 1-x-y Co x M y O 2+z
[0026] In the above general formula (1), M is one or more elements selected from Mg, Ca, Sr, Ba, Al, Ti, V, Cr, Mn, Fe, Cu, Zr, Nb, Mo, W, Ta, Si, P, and B; 0.9≦a≦1.2, 0.01≦x≦0.5, 0.01≦y≦0.5, 0.02≦x+y<1, −0.1≦z≦0.1 is satisfied.
[0027] In the above general formula (1), the value of a indicating the lithium content is 0.9 or more and 1.2 or less, may be 0.95 or more and 1.2 or less, and more preferably 1.0 or more and 1.1 or less. When the value of a is within the above range, the output characteristics and capacity characteristics of a secondary battery using the positive electrode active material 10 can be improved. Specifically, by setting the value of a to 0.9 or more, the internal resistance of a secondary battery using the positive electrode active material 10 can be suppressed and the output characteristics can be improved. In addition, by setting the value of a to 1.2 or less, the initial discharge capacity of a secondary battery using the positive electrode active material 10 can be maintained high.
[0028] In the general formula (1) above, (1 - x - y) indicating the nickel content is greater than 0 and less than or equal to 0.98, and may be greater than or equal to 0.3 and less than or equal to 0.98, or may be greater than or equal to 0.5 and less than or equal to 0.98. Also, the lower limit of the nickel content may be greater than or equal to 0.6, may be greater than or equal to 0.7, or may be greater than or equal to 0.8. The higher the content ratio of (1 - x - y), the lower the voltage required for charging, and as a result, the higher the battery capacity.
[0029] In the general formula (1) above, x indicating the cobalt content is greater than or equal to 0.01 and less than or equal to 0.5, and may be greater than or equal to 0.01 and less than or equal to 0.3, or may be greater than or equal to 0.05 and less than or equal to 0.2. When the cobalt content is within the above range, the charge-discharge cycle characteristics and output characteristics can be improved.
[0030] In the general formula (1) above, the element M is one or more elements selected from Mg, Ca, Sr, Ba, Al, Ti, V, Cr, Mn, Fe, Cu, Zr, Nb, Mo, W, Ta, Si, P, and B. Also, the element M preferably contains at least one element selected from Al and Mn, and preferably contains Al. The element M can be appropriately selected according to the use and required performance of the secondary battery configured using the positive electrode active material 10.
[0031] y indicating the content ratio of the element M in the above substance quantity ratio is 0 < y ≤ 0.5, preferably 0 < y ≤ 0.3, and may be 0 < y ≤ 0.2. For example, when the element M contains Al, the range of Al (y1) may be, for example, 0 < y1 ≤ 0.1, or may be 0 < y1 ≤ 0.05.
[0032] (Crystal structure) The lithium transition metal composite oxide 1 preferably has a layered rock-salt crystal structure. When the lithium transition metal composite oxide 1 has a layered rock-salt crystal structure, the lithium transition metal composite oxide 1 can have a high battery capacity in a secondary battery. The crystal structure of the lithium transition metal composite oxide 1 can be confirmed by powder X-ray diffraction (XRD) measurement. Specifically, it is preferable that a peak belonging to a layered rock-salt crystal structure of the "R-3m" structure (a crystal structure belonging to the space group R-3m) is detected from the diffraction pattern obtained by performing powder X-ray diffraction (XRD) measurement of the lithium transition metal composite oxide 1. In particular, it is more preferable that only a peak belonging to a layered rock-salt crystal structure of the "R-3m" structure is detected from the diffraction pattern.
[0033] (particle structure) The lithium transition metal composite oxide 1 is composed of secondary particles formed by agglomeration of a plurality of primary particles. The structure of the secondary particles of the lithium transition metal composite oxide 1 is not particularly limited, but is preferably a solid structure in which the primary particles are densely arranged. For example, the porosity of the lithium transition metal composite oxide 1 (the ratio of the void area inside the secondary particles to the cross-sectional area of the secondary particles) may be less than 15%, 10% or less, 5% or less, or 2% or less.
[0034] The porosity can be measured by observing an arbitrary cross section (a cross section of a secondary particle having a cross section major axis of the volume average particle diameter Mv±20%) of the lithium transition metal composite oxide 1 using a scanning electron microscope and analyzing the image. For example, a plurality of particles of the lithium transition metal composite oxide 1 are embedded in a resin or the like, and the cross section of the particle is made observable by a cross section polisher or the like. Then, using image analysis software such as WinRoof 6.1.1, the voids in the secondary particles (parts where no primary particles exist) are measured as black, and the dense parts in the outlines of the secondary particles (parts where primary particles exist) are measured as white, and the porosity can be obtained by calculating the area of [black parts / (black parts+white parts)] for any 20 or more particles.
[0035] (Volume average particle size) The volume average particle diameter Mv of the lithium transition metal composite oxide 1, as measured by a laser diffraction scattering type particle size distribution analyzer, is preferably 1 μm or more and 10 μm or less, more preferably 2 μm or more and 7 μm or less, and even more preferably 3 μm or more and 5 μm or less. This is because, when the volume average particle diameter of the lithium transition metal composite oxide particles is 1 μm or more and 10 μm or less, the battery capacity per volume can be sufficiently increased in a secondary battery using a positive electrode active material 10 containing the lithium transition metal composite oxide 1 in the positive electrode.
[0036] (2) Covering layer The positive electrode active material 10 has a coating layer 2 on the surface of a lithium transition metal composite oxide 1. By having the coating layer 2 on the surface of the lithium transition metal composite oxide 1, in a secondary battery having a positive electrode containing the positive electrode active material 10, it is possible to suppress mutual reaction between the positive electrode active material 10 and a solid electrolyte.
[0037] The coating layer 2 includes a compound containing lithium and tungsten, and may be formed of, for example, a compound consisting of lithium, tungsten, and oxygen. Examples of the compound containing lithium and tungsten include Li2WO4, 7Li2WO4·4H2O, Li4WO5, and the like, and may include Li4WO5 having a rock salt structure (space group: Fm-3m). The type of the compound containing lithium and tungsten can be confirmed from the diffraction pattern of X-ray diffraction (XDR). Specifically, it is preferable that at least one of a peak belonging to Li2WO4 having an "R-3" structure, a peak belonging to 7Li2WO4·4H2O having a "P-43m" structure, and a peak belonging to Li4WO5 having an "Fm-3m" structure is detected from the diffraction pattern obtained when the powder X-ray diffraction (XRD) measurement of the positive electrode active material 10 is performed.
[0038] The coating layer 2 refers to a portion (region) in the surface region (surface layer) of the positive electrode active material 10 that has a higher concentration of tungsten (W element) than the lithium transition metal composite oxide 1 (center region) that is the coated material. The coating layer 2 and the lithium transition metal composite oxide 1 may or may not have a clear boundary line. For example, the coating layer 2 may be partially dissolved in the lithium transition metal composite oxide 1.
[0039] (Tungsten coverage) The tungsten coverage P can be calculated from semi-quantitative analysis by X-ray photoelectron spectroscopy (XPS) using the following formula 1. The tungsten coverage P indicates the extent of the coverage area of the lithium transition metal composite oxide of the coating layer 2 relative to the secondary particle surface (the coverage rate of the coating layer containing lithium and tungsten relative to the secondary particle surface).
[0040] P=(W / (W+Ni+Co+M))×100...(Formula 1)
[0041] In the above formula 1, W is the amount of tungsten determined by XPS analysis. Ni is the amount of nickel determined by XPS analysis. Co is the amount of cobalt determined by XPS analysis. M is the amount of element M (excluding tungsten) quantified by XPS analysis Shows.
[0042] The XPS analysis is a value obtained from the intensity (area) ratio of peaks derived from each metal element in the XPS spectrum obtained when lithium transition metal composite oxide 1 is measured by X-ray photoelectron spectroscopy (XPS) using an X-ray photoelectron spectrometer (Versa Probe II, manufactured by ULVAC-PHI) with a monochromatic Al-Kα X-ray source, an X-ray beam width of 100 μm, and an output of 25 W. Since XPS analysis has the characteristic of being able to selectively obtain information from the surface of the measurement target from 1 nm to 5 nm, it is possible to know the composition ratio of the surface layer of the material (within the range of 1 to 5 nm from the surface).
[0043] The tungsten coverage P is 30% or more, preferably 60% or more, and more preferably 80% or more. By setting the tungsten coverage P of the coating layer in the above range, a high discharge capacity is obtained, and the effect of preventing both the interfacial reaction between the lithium transition metal composite oxide and the solid electrolyte and the interfacial mixing between the lithium transition metal composite oxide and the coating layer is exhibited, thereby suppressing deterioration during cycles.
[0044] The upper limit of the coverage of tungsten is not particularly limited, and may be 100% or less, and may be 100% or less than 95%. In addition, when using the manufacturing method described later, it is possible to obtain a positive electrode active material 10 having a high discharge capacity even if the coverage of tungsten is 90% or less.
[0045] (Tungsten content) The content of tungsten in the positive electrode active material 10 is not particularly limited, and can be appropriately adjusted to satisfy the above coverage rate. The content of tungsten may be, for example, 0.1% by mass or more and 6% by mass or less, more than 1% by mass or less and 5% by mass or less, or 1.5% by mass or more and 4% by mass or less, relative to the total amount of the positive electrode active material 10. When the content of tungsten is within the above range, a coating layer can be formed uniformly over the entire surface of the lithium transition metal composite oxide 1. In addition, tungsten may be present as a compound containing tungsten between primary particles inside the secondary particles.
[0046] (average thickness of coating layer) The average thickness of the coating layer is, for example, preferably 2 nm or more and 20 nm or less, more preferably 2 nm or more and 15 nm or less, and even more preferably 5 nm or more and 15 nm or less.
[0047] The average thickness of the coating layer 2 can be calculated by observing the layer uniformly formed on the surface of the lithium transition metal composite oxide 1 using a scanning electron microscope (SEM) or a transmission electron microscope (TEM), or analyzing the layer using a spectrometer such as an energy dispersive X-ray spectrometer (EDS) or an electron energy loss spectroscopy (EELS) attached to the SEM or TEM. When the thickness of the coating layer 2 varies depending on the measurement site, the thickness of the coating layer 2 refers to the average value of the measurements taken at multiple sites. The average thickness of the coating layer 2 can also be calculated simply from the specific surface area, coverage, and tungsten content of the lithium transition metal composite oxide 1.
[0048] (3) Positive electrode active material The positive electrode active material 10 has the above-mentioned lithium transition metal composite oxide 1 and the coating layer 2, and is preferably composed only of particles of the lithium transition metal composite oxide 1 and the coating layer 2. In addition, the positive electrode active material 10 preferably has the following properties.
[0049] (moisture content) Impurities may be mixed into the positive electrode active material 10 during the manufacturing process. Examples of impurities include moisture. Moisture is an impurity that may increase in the positive electrode active material 10 due to treatment using water or an aqueous solution in the coating process. Moisture may cause hydrolysis and deterioration of the solid electrolyte and affect the initial discharge capacity, so it is preferable that the moisture content is controlled within a predetermined range.
[0050] The positive electrode active material 10 preferably has a water content (water content) of 0.08% by mass or less with respect to the total amount of the positive electrode active material 10. By setting the water content to 0.08% by mass or less, the hydrolysis reaction of the solid electrolyte can be more reliably suppressed in a solid secondary battery using the positive electrode active material 10. Furthermore, when the solid electrolyte is hydrolyzed, hydrogen sulfide is generated, which deteriorates the solid electrolyte and reduces the lithium ion conductivity. However, by setting the water content of the positive electrode active material 10 to 0.08% by mass or less, the hydrolysis reaction of the solid electrolyte can be more reliably suppressed, and the deterioration can be suppressed.
[0051] The moisture content of the positive electrode active material 10 can be evaluated, for example, by the Karl Fischer method at a heating temperature of 300° C. The lower limit of the moisture content of the positive electrode active material 10 is not particularly limited, but is, for example, 0.001% by mass or more.
[0052] (specific surface area) The specific surface area of the positive electrode active material 10 is not particularly limited and is, for example, 0.3 m 2 / g or more 2.0m 2 / g or less, and 2 / g or more 1.0m 2 / g or less. When the specific surface area is in the above range, the output characteristics are good. The specific surface area can be measured by a nitrogen adsorption BET method. The specific surface area of the positive electrode active material 10 is, for example, 0.8 m 2 / g or less.
[0053] (Pore volume and average pore diameter) The pore volume diameter of the positive electrode active material 10 is not particularly limited, but is, for example, 0.001 cm 3 / g or more 0.008cm 3 / g or less, and 3 / g or more 0.004cm 3 / g or less. When the pore volume is in the above range, the added tungsten can be sufficiently infiltrated not only into the surface of the secondary particles but also into the interior, forming a uniform coating layer on the surface of the secondary particles, and forming a compound containing tungsten inside the secondary particles. In an all-solid-state lithium-ion secondary battery, the solid electrolyte does not enter the interior of the secondary particles of the positive electrode active material, so that lithium ions cannot diffuse through the voids inside the secondary particles. When the pore volume is in the above range, it is considered that the proportion of voids is small, and therefore the resistance of the battery is reduced.
[0054] The average pore size (diameter) of the positive electrode active material 10 may be, for example, 1 nm or more and 10 nm or less, or 1 nm or more and 4 nm or less. When the average pore size is in the above range, the added tungsten can be efficiently infiltrated into the surface and the inside of the secondary particles. The pore volume size and the average pore size can be measured by the Barrett-Joyner-Halenda (BJH) method.
[0055] 2. Manufacturing method of positive electrode active material for all-solid-state lithium-ion secondary batteries The manufacturing method of the positive electrode active material 10 is not particularly limited as long as it can produce a positive electrode active material having the above-mentioned characteristics. For example, the above-mentioned positive electrode active material 10 can be manufactured with high productivity by using the following manufacturing method.
[0056] The method for producing the positive electrode active material 10 includes, for example, a dispersion step (S10) of dispersing a lithium transition metal composite oxide (base material) in pure water or an LiOH aqueous solution to obtain a positive electrode active material slurry, a separation step (S20) of dehydrating the positive electrode active material slurry to obtain a washed cake, a mixing step (S30) of mixing the washed cake with a compound (powder) containing tungsten to obtain a mixture, and a drying step (S40) of drying the mixture.
[0057] [Dispersion process (S10)] The dispersion step (S10) is a step of mixing the lithium transition metal composite oxide (base material) with water or an aqueous solution to obtain a positive electrode active material slurry. The dispersion step (S10) removes impurities (such as excess lithium and sulfate radicals) present on the surfaces of the primary particles of the lithium transition metal composite oxide (base material) and on the grain boundaries between the primary particles, and by wetting the entire surface of the lithium transition metal composite oxide (base material) with water or an aqueous solution, adhesion of the compound containing tungsten, which is added in a later step, to the surfaces and inside of the secondary particles is promoted, and a more uniform coating layer 2 can be formed.
[0058] The lithium transition metal composite oxide used as the base material may be one obtained by using a known technique. For example, the lithium transition metal composite oxide (base material) may be obtained by mixing a nickel composite hydroxide obtained by co-precipitating (crystallizing) metal elements (other than lithium) constituting the lithium transition metal composite oxide, or a nickel composite oxide obtained by further heat-treating this nickel composite hydroxide (hereinafter, these are also collectively referred to as "precursors") with a lithium compound, and then calcining the resulting lithium mixture.
[0059] The lithium transition metal composite oxide (base material, before coating) may have the same composition as the lithium transition metal composite oxide 1 contained in the positive electrode active material 10. The lithium transition metal composite oxide (base material) may have a BET specific surface area after the dispersion step (S10) larger than the BET specific surface area before the dispersion step (S10), for example, 1.0 m 2 / g or more 2.0m 2 / g or less. In addition, the lithium transition metal composite oxide (base material) may have a pore volume after the dispersion step (S10) larger than the pore volume before the dispersion step (S10). For example, the pore volume after the dispersion step (S10) may be 0.005 cm 3 / g or more 0.01cm 3 / g or less. Furthermore, the average pore size after the dispersion step (S10) may be 1 nm or more and 10 nm or less.
[0060] The dispersion step may be carried out by a known method and under known conditions, and may be carried out within a range in which lithium is not excessively eluted from the surface of the lithium transition metal composite oxide (base material) and the battery characteristics are not deteriorated. For example, the slurry concentration of the positive electrode active material can be appropriately adjusted within a range of 500 g / L or more and 2500 g / L or less.
[0061] The water or aqueous solution used in the dispersion step (S10) is not particularly limited, but it is preferable to use an aqueous solution containing Li, and it is preferable to use an aqueous solution of lithium hydroxide. By using an aqueous solution of lithium hydroxide, a sufficient amount of lithium can be supplied to the surface of the secondary particles of the lithium transition metal composite oxide (base material) and the inside of the secondary particles (voids between primary particles and incomplete grain boundaries) that communicate with the outer surface of the secondary particles, and the reaction with the tungsten compound in the drying step (S40) can be promoted and other impurities can be efficiently removed. The concentration of the aqueous solution of lithium hydroxide can be appropriately adjusted, for example, within a range of 0.5 g / L or more and 35 g / L or less in terms of lithium weight.
[0062] [Solid-liquid separation process (S20)] The solid-liquid separation step (S20) is a step of dehydrating the positive electrode active material slurry to obtain a washed cake. The slurry is subjected to solid-liquid separation to obtain a washed cake containing the lithium nickel composite oxide. The method of dehydrating the positive electrode active material slurry is not particularly limited, and for example, the slurry is dehydrated by solid-liquid separation using a suction filter, a centrifuge, a filter press, or the like.
[0063] The water content of the washed cake may be, for example, in the range of 2% by mass or more and 15% by mass or less.
[0064] [Mixing process (S30)] The mixing step (S30) is a step of mixing the washed cake with a powder of a tungsten compound to obtain a mixture. The mixing step (S30) allows the tungsten compound to penetrate into the surface of the lithium transition metal composite oxide (base material) and into the interior of the base material that is permeable to water or an aqueous solution, so that tungsten can be uniformly dispersed on the surfaces of the secondary particles and inside the secondary particles (gaps between primary particles and interfaces) in the lithium transition metal composite oxide 1.
[0065] [Drying process (S40)] The drying step (S40) is a step of drying the mixture obtained in the mixing step (S30). In the drying step (S40), a compound containing tungsten and lithium is formed from W supplied from the tungsten compound and Li supplied from the aqueous solution of the slurry of the positive electrode active material or Li dissolved from the lithium transition metal composite oxide (base material), and a positive electrode active material 10 can be obtained in which a coating layer 2 is uniformly formed on the surface of the secondary particles of the lithium transition metal composite oxide 1. In addition, the obtained positive electrode active material 10 may have a smaller specific surface area and / or pore volume than the lithium transition metal composite oxide (base material) after the dispersion step (S10) and before the mixing step (S30).
[0066] The drying conditions may be any conditions that can sufficiently reduce the moisture content in the mixture, and for example, the drying temperature may be 80° C. or higher and 110° C. or lower. After the drying step (S40), a heat treatment step may be carried out at a temperature higher than that of the drying step.
[0067] 3. All-solid-state lithium-ion secondary battery The all-solid-state lithium ion secondary battery (hereinafter also referred to as "all-solid-state battery") according to this embodiment includes a positive electrode, a negative electrode, and a solid electrolyte, and contains a positive electrode active material 10 in the positive electrode. The positive electrode may contain a positive electrode active material other than the above-mentioned positive electrode active material 10, for example, may contain a single primary particle, or may be a mixture of a single primary particle and a secondary particle. The positive electrode may also contain a positive electrode active material having a composition or particle size different from that of the above-mentioned positive electrode active material 10. Hereinafter, the all-solid-state battery according to this embodiment will be described for each component.
[0068] The embodiments described below are merely illustrative, and the all-solid-state battery can be embodied in various forms, including the following embodiments, with various modifications and improvements based on the knowledge of those skilled in the art. In addition, the use of the all-solid-state battery is not particularly limited.
[0069] (positive electrode) The positive electrode can be formed by molding the positive electrode mixture. The positive electrode can be appropriately processed according to the battery to be used. For example, the positive electrode can be subjected to a compression treatment using a press or the like to increase the electrode density.
[0070] The above-mentioned positive electrode mixture can be formed by mixing the above-mentioned positive electrode active material in powder form with a solid electrolyte.
[0071] The solid electrolyte is added to the electrode to provide it with suitable ionic conductivity. The material of the solid electrolyte is not particularly limited, but may be, for example, Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 Sulfide-based solid electrolytes such as Li7La3Zr2O 12 , Li 0.34 La 0.51 TiO 2.94 For example, an oxide-based solid electrolyte such as SiO2 or a polymer-based electrolyte such as PEO can be used.
[0072] A binder and a conductive assistant may also be added to the positive electrode mixture.
[0073] The binder plays a role of binding the positive electrode active material. The binder used in the positive electrode mixture is not particularly limited, but may be one or more selected from the group consisting of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose-based resin, polyacrylic acid, and the like.
[0074] The conductive material is added to the electrode to give it suitable electrical conductivity. The material of the conductive material is not particularly limited, but examples of the conductive material include graphite such as natural graphite, artificial graphite, and expanded graphite, and carbon black materials such as acetylene black and Ketjen Black (registered trademark).
[0075] The mixing ratio of each material in the positive electrode mixture is not particularly limited. For example, the positive electrode mixture may contain 50 parts by mass or more of the positive electrode active material and 90 parts by mass or less of the solid electrolyte, and the positive electrode mixture may contain 10 parts by mass or more and 50 parts by mass or less of the positive electrode active material.
[0076] However, the method for producing the positive electrode is not limited to the above-mentioned example, and other methods may be used.
[0077] (Negative electrode) The negative electrode can be formed by molding a metal (lithium metal, indium metal, lithium-indium alloy, lithium-aluminum alloy, Si or an alloy containing Si, etc.) or a negative electrode mixture. Although the components constituting the negative electrode mixture and the composition thereof are different, the negative electrode mixture is formed in substantially the same manner as the positive electrode described above, and is subjected to various treatments as necessary in the same manner as the positive electrode. The negative electrode mixture can be prepared by mixing a negative electrode active material and a solid electrolyte. As the negative electrode active material, for example, an occlusion material capable of occluding and desorbing lithium ions can be used. The storage material is not particularly limited, and may be one or more selected from, for example, natural graphite, artificial graphite, organic compound sintered bodies such as phenolic resin, and powders of carbon materials such as coke. When such a storage material is used as the negative electrode active material, a sulfide electrolyte such as Li3PS4 may be used as the solid electrolyte, as in the positive electrode.
[0078] (solid electrolyte) The solid electrolyte is Li + A solid electrolyte that has ion conductivity. As the solid electrolyte, one selected from oxides, sulfides, polymers, etc. can be used alone or in combination of two or more.
[0079] There are no particular limitations on the oxide-based solid electrolyte, and any oxide-based solid electrolyte that contains oxygen (O) and has lithium ion conductivity and electronic insulation properties can be used.
[0080] Examples of oxide-based solid electrolytes include lithium phosphate (Li3PO4), Li3PO4NX, LiBO2NX, LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≦X≦1), Li 1+X Al X Ge 2-X (PO4)3(0≦X≦1), LiTi2(PO4)3, Li3XLa 2 / 3-X TiO3(0≦X≦2 / 3), Li5La3Ta2O 12 , Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , Li 3.6 S 0.6 P 0.4 Examples include O4.
[0081] The sulfide-based solid electrolyte is not particularly limited, and any electrolyte that contains sulfur (S) and has lithium ion conductivity and electronic insulation can be used. Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, and LiI-Li3PO4-P2S5.
[0082] As the inorganic solid electrolyte, materials other than those mentioned above may be used, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. may be used.
[0083] The polymer solid electrolyte is not particularly limited as long as it is a polymer compound exhibiting ion conductivity, and for example, polyethylene oxide, polypropylene oxide, and copolymers thereof can be used. The organic solid electrolyte may also contain a supporting salt (lithium salt). When using a solid electrolyte, the solid electrolyte may also be mixed into the positive electrode material to ensure contact between the electrolyte and the positive electrode active material.
[0084] (Shape and structure of all-solid-state batteries) Next, an example of the arrangement and configuration of components of the all-solid-state battery according to this embodiment will be described. The all-solid-state battery composed of the above positive electrode, negative electrode, and solid electrolyte can be formed into various shapes, such as a coin shape or a laminated shape, that can be subjected to a certain pressure. In any shape, the positive electrode and the negative electrode can be laminated via the solid electrolyte. Then, the positive electrode current collector and the positive electrode terminal that leads to the outside, and the negative electrode current collector and the negative electrode terminal that leads to the outside can be connected using a current collecting lead or the like, and the battery can be sealed in a battery case to form an all-solid-state battery.
[0085] (Characteristics of all-solid-state batteries) The all-solid-state battery according to this embodiment using the positive electrode active material 10 can have a charge / discharge capacity equivalent to that of a lithium ion secondary battery using an electrolyte solution. For example, when the positive electrode active material 10 of this embodiment is used in the positive electrode to configure a test battery shown in Fig. 2, the initial discharge capacity measured under the conditions of the example may be 110% or more, 130% or more, 150% or more, or 170% or more of the initial discharge capacity of a lithium transition metal composite oxide produced under similar conditions except that a coating layer is not formed.
[0086] The use of the secondary battery of this embodiment is not particularly limited, and it can be suitably used for various uses requiring a power source. In addition, since the secondary battery of this embodiment has a charge / discharge capacity equivalent to that of a lithium ion battery using an electrolyte and can be miniaturized, it can be suitably used as a power source for electric vehicles that are limited in terms of mounting space. EXAMPLES
[0087] The present invention will be specifically described below using examples and comparative examples.
[0088] [Example 1] 1. Lithium transition metal composite oxide A lithium transition metal composite oxide having the following physical properties was prepared using a known method. (a) Chemical composition The chemical composition of the lithium transition metal composite oxide was quantitatively analyzed using an ICP emission spectrometer (VARIAN, 725ES) and found to have a mass ratio of Li, Ni, Co, and Al of Li:Ni:Co:Al=1.03:0.82:0.15:0.03. (b) Crystal structure The crystal structure of the lithium transition metal composite oxide was measured using XRD (X'Pert, PROMRD, manufactured by PANALYTICAL Corporation), and was found to have a layered rock-salt structure belonging to the R-3m structure. (c) Specific surface area The BET specific surface area of the lithium transition metal composite oxide was measured using a fully automated BET specific surface area measuring device (Maxsorb, manufactured by Mountec Co., Ltd.) and found to be 0.60 m 2 / g. (d) Volume average particle size The volume average particle size of the lithium transition metal composite oxide was measured using a laser diffraction scattering type particle size distribution measuring device (Microtrack HRA, manufactured by Nikkiso Co., Ltd.) and found to be 5.1 μm. 2.Coating layer formation Li 1.03 Ni 0.80 Co 0.15 Al 0.05 The lithium transition metal composite oxide powder of O2 was subjected to the following coating process to produce a positive electrode active material.
[0089] The lithium transition metal composite oxide was dispersed in an aqueous LiOH solution to prepare a positive electrode active material slurry, which was then dehydrated to obtain a positive electrode active material cake (water content: 5.8% by mass). The positive electrode active material cake was mixed with WO3, vacuum dried, and sieved to obtain a positive electrode active material. The obtained positive electrode active material was evaluated by the following method.
[0090] 3. Evaluation of positive electrode active material (a) Composition The composition was analyzed using an ICP emission spectrometer (VARIAN, 725ES). This analysis revealed that this positive electrode active material contained 1.7 wt% W. In addition, the moisture content of the positive electrode active material was measured by the Karl Fischer method at a heating temperature of 300°C, and the moisture content was 0.08 mass%.
[0091] (b) Evaluation of coverage (surface analysis) The positive electrode active material was measured by XPS (ULVAC-PHI, Versa Probe II), and the amount of material (at%) on the positive electrode active material surface was obtained from the semi-quantitative values calculated from the peak areas of the Ni=2p3 / 2 spectrum, Co=2p3 / 2 spectrum, Al=2p spectrum, W=4f7 / 2 spectrum, and Nb=3d5 / 2 spectrum. The W coverage, which is the ratio of W present on the surface to the sum of Ni, Co, Al, and W, was (W) / (Ni+Co+Al+W)×100=33%. The Nb coverage, which is the ratio of Nb present on the surface to the sum of Ni, Co, Al, and Nb, was (Nb) / (Ni+Co+Al+Nb)×100=0%.
[0092] In addition, when the crystal structure of the positive electrode active material was measured using XRD (D8 DISCOVER Vario-1, manufactured by Bruker Japan), peaks belonging to a lithium transition metal composite oxide (R-3m) and peaks belonging to Li2WO4, 7Li2WO4·4H2O, and Li4WO5 were detected.
[0093] (c) Thickness of the coating layer The thickness of the coating layer was calculated from the amount of W contained in the positive electrode active material, the coverage of W, and the BET specific surface area of the positive electrode active material. The BET specific surface area was measured using a fully automatic BET specific surface area measuring device (Maxsorb, manufactured by Mountec Co., Ltd.).
[0094] (d) Pore volume and average pore diameter The pore volume and average pore size (diameter) were calculated by the Barrett-Joyner-Halenda (BJH) method from the nitrogen adsorption isotherm measured using an independent 4-station specific surface area and pore size distribution analyzer (QUADRASORB SI, manufactured by Quantachrome Instruments). In the BJH method, the pore shape is assumed to be cylindrical, and the pore size distribution is obtained from the relationship between the pore size at which capillary condensation occurs and the relative pressure of nitrogen (Kelvin equation).
[0095] 4. Preparation of all-solid-state batteries (test batteries) For the battery evaluation of the positive electrode active material, a battery (hereinafter referred to as the "test battery") having the structure shown in Fig. 2 was used. As shown in Fig. 2, the test battery SBA is composed of a case having a negative electrode can NC and a positive electrode can PC, and a compacted cell C housed in the case.
[0096] The case includes a negative can NC that is hollow and has one open end, and a positive can PC that is placed in the opening of the negative can NC. When the positive can PC is placed in the opening of the negative can NC, a space is formed between the positive can and the negative can NC to house the compacted cell C. The positive can PC is fixed to the negative can NC with a thumbscrew SW and a nut N.
[0097] The negative can NC has the negative terminal, and the positive can PC has the positive terminal. The case is equipped with an insulating sleeve ISV, which fixes the negative can NC and the positive can PC so that they are kept out of contact with each other.
[0098] A pressure screw PSW is provided at the closed end of the negative can NC, and after the positive can PC is fixed to the negative can NC, the pressure screw PSW is tightened toward the storage space of the compacted cell C, thereby holding the compacted cell C in a pressurized state through a hemispherical washer W. A screw-in plug P is provided at the end of the negative can NC where the pressure screw PSW is located. O-rings OL are provided between the negative can NC and the positive can PC, and between the negative can NC and the plug P, which seal the gap between the negative can NC and the positive can PC and maintain an airtight seal inside the case.
[0099] The compact cell C is a pellet consisting of a positive electrode layer PL, a solid electrolyte layer SEL, and a negative electrode layer NL, stacked in that order. The positive electrode layer PL contacts the inner surface of the positive electrode can PC through the lower current collector LCC, and the negative electrode layer NL contacts the inner surface of the negative electrode can NC through the upper current collector UCC, a hemispherical washer W, and a pressure screw PSW. The lower current collector LCC, compact cell C, and upper current collector UCC are protected by a sleeve SV to prevent electrical contact between the positive electrode layer PL and the negative electrode layer NL.
[0100] The above test battery SBA was prepared as follows.
[0101] First, 60 mg of the positive electrode active material and 40 mg of the solid electrolyte Li3PS4 were mixed in a mortar to prepare a positive electrode mixture. Next, a molding die capable of producing pellets with a diameter of 10 mm was prepared, and (1) 60 mg of the solid electrolyte was added and pressed at 10 MPa. (2) An additional 15 mg of the positive electrode mixture was added and pressed at 360 MPa to obtain a two-layer pellet consisting of a tightly bonded positive electrode layer PL and solid electrolyte layer.
[0102] Starting from the bottom, the lower current collector LCC, the pellet with the positive electrode layer PL facing downwards, indium foil (negative electrode layer NL), and the upper current collector UCC were layered in that order to form the electrode (compressed powder cell C), which was then sealed in the case, and the pressure screw PSW was tightened with a torque of 5 to 7 N m to provide a restraining force. The test battery was fabricated in a glove box with an Ar atmosphere and a controlled dew point of -80°C.
[0103] 5. Evaluation of Solid-State Secondary Batteries The charge / discharge capacity of the test battery was measured under the following conditions.
[0104] The test battery SBA was placed in a thermostatic chamber at 25°C, and after the open circuit voltage OCV (Open Circuit Voltage) stabilized, it was charged to a cutoff voltage of 4.3V (vs. Li+ / Li) so that the current value per 1g of active material was 19mA / g, and then charging was continued at 4.3V (vs. Li+ / Li) until the current value per 1g of active material was 1.9mA / g. After a one-hour break, it was discharged to a cutoff voltage of 3.0V (vs. Li+ / Li) so that the current value per 1g of active material was 19mA / g, and then charging was continued at 3.0V (vs. Li+ / Li) until the current per 1g of active material was 1.9mA / g.
[0105] The above evaluation results are shown in Table 1. The discharge capacity shown in Table 1 is a relative ratio with the discharge capacity of Comparative Example 1 as the reference (100%), and a relative discharge capacity ratio exceeding 100% indicates that the discharge capacity was increased compared to the uncoated product of Comparative Example 1. The relative discharge capacity ratio of Example 1 was 111%. Furthermore, when a cross section of the positive electrode active material of Example 1 was analyzed, compounds containing tungsten were confirmed between the primary particles inside the secondary particles.
[0106] [Example 2] A positive electrode active material was prepared and evaluated under the same conditions as in Example 1 except for changing the amount of WO3 added. As a result, the W coverage was 61%, the Nb coverage was 0%, and the discharge capacity relative ratio to Comparative Example 1 was 139%. The results are shown in Table 1.
[0107] [Example 3] A positive electrode active material was prepared and evaluated under the same conditions except for changing the amount of WO3 added in Example 1. As a result, the W coverage rate was 89%, the Nb coverage rate was 0%, and the discharge capacity relative ratio to Comparative Example 1 was 174%. The results are shown in Table 1.
[0108] [Example 4] A positive electrode active material was prepared and evaluated under the same conditions as in Example 1 except for changing the amount of WO3 added. As a result, the W coverage was 91%, the Nb coverage was 0%, and the discharge capacity relative ratio to Comparative Example 1 was 151%. The results are shown in Table 1.
[0109] [Comparative Example 1] A positive electrode active material was prepared and evaluated under the same conditions as in Example 1, except that the step of forming the coating layer was omitted. As a result, the W coverage rate was 0%, and the Nb coverage rate was 0%. The discharge capacity of Comparative Example 1 was set to 100%, which is the standard for the relative ratio. The results are shown in Table 1.
[0110] [Comparative Example 2] All were produced in the same manner as in Example 1 except that the amount of WO3 added was changed. As a result, the W coverage rate was 13%, the Nb coverage rate was 0%, and the discharge capacity relative ratio to Comparative Example 1 was 74%. The results are shown in Table 1.
[0111] [Comparative Example 3] A positive electrode active material was produced and evaluated under the same conditions as in Example 1 except that the process of forming the coating layer (containing tungsten) was changed and the coating layer (containing niobium) was formed in the following process. As a result, the W coverage was 0%, the Nb coverage was 83%, and the discharge capacity relative ratio to Comparative Example 1 was 124%. The results are shown in Table 1.
[0112] (Niobium coating process) 500 g of lithium transition metal composite oxide powder was weighed out and fluidized in a tumbling fluidized granulation coating device (Powrex, MP-01), and a mixed aqueous solution adjusted to a Li / Nb ratio of 1.0 was sprayed into the fluidized tank, while the temperature of the air supplied into the fluidized tank was controlled to 120°C, and a coating process was carried out slowly over 4 hours to form a coating layer on the surface of the powder. The obtained powder was collected and then heat-treated in an oxygen atmosphere at 300°C for 2 hours to produce a lithium transition metal composite oxide with a coating layer made of Li and Nb from which moisture had been completely removed.
[0113] [Comparative Example 4] A positive electrode active material was prepared and evaluated under the same conditions as in Example 1 except that in the coating layer formation step, WO3 was not mixed and the material was dried as is. As a result, the W coating rate was 0%, the Nb coating rate was 0%, and the discharge capacity relative ratio to Comparative Example 1 was 16%. The results are shown in Table 1. [Table 1]
[0114] [Evaluation Results] The positive electrode active materials of the Examples had significantly improved initial discharge capacities, as compared with the positive electrode active material of Comparative Examples 1 and 4 having no coating layer, and the positive electrode active material of Comparative Example 2 having a low W coverage.
[0115] In addition, the positive electrode active materials of Examples 2 to 4 (W coverage of 61 to 91%) were shown to have higher initial discharge capacities than the positive electrode active material of Comparative Example 3 (Nb coverage of 83%) coated with a compound containing lithium and niobium.
[0116] Moreover, in Comparative Example 4, in which a tungsten compound was not mixed into the positive electrode active material slurry in the coating layer formation step, the initial discharge capacity was significantly reduced compared to Comparative Example 1, in which the coating layer formation step was not performed.
[0117] According to the present invention, it is possible to provide a positive electrode active material that can be suitably used for the positive electrode of an all-solid-state lithium ion secondary battery that requires a high battery capacity. [Explanation of symbols]
[0118] 1...Lithium transition metal composite oxide 2…Covering layer 10...Cathode active material SBA…Test battery PC…Positive electrode can NC: Negative electrode can ISV…insulating sleeve C…Powder compact cell PL…Positive electrode layer NL…Negative electrode layer SEL…Solid electrolyte layer LCC: Lower current collector UCC: Upper current collector P…Plug PSW…Pressure screw W…Semi-spherical washer OL...O-ring SV…Sleeve SW…Screw N…Nut
Claims
1. A positive electrode active material for an all-solid-state lithium ion secondary battery, comprising: a lithium transition metal composite oxide composed of secondary particles formed by agglomeration of a plurality of primary particles; and a coating layer that coats the surfaces of the secondary particles, The lithium transition metal composite oxide contains lithium, nickel, and optionally cobalt, and an element M (wherein the element M is an added element other than lithium, nickel, cobalt, and oxygen), the coating layer includes a compound including at least lithium and tungsten, The coverage P (%) of tungsten on the secondary particle surface, calculated by the following (Equation 1), is 30% or more and 95% or less. Positive electrode active material for all-solid-state lithium-ion secondary batteries. P=(W / (W+Ni+Co+M))×100(%)...(Formula 1) W: Amount of tungsten determined by X-ray photoelectron spectroscopy (XPS analysis) Ni: The amount of nickel determined by X-ray photoelectron spectroscopy (XPS analysis) Co: Amount of cobalt determined by X-ray photoelectron spectroscopy (XPS analysis) M: The amount of element M (excluding tungsten) quantified by X-ray photoelectron spectroscopy (XPS analysis)
2. The positive electrode active material for an all-solid-state lithium ion secondary battery according to claim 1 , wherein the lithium transition metal composite oxide is represented by the following formula 2: Li a Ni 1-x-y Co x M y O 2+z … (Formula 2) Here, M is one or more elements selected from Mg, Ca, Sr, Ba, Al, Ti, V, Cr, Mn, Fe, Cu, Zr, Nb, Mo, W, Ta, Si, P, and B, and satisfies 0.9≦a≦1.2, 0.01≦x≦0.5, 0.01≦y≦0.5, 0.02≦x+y<1.0, and −0.1≦z≦0.
1.
3. 3. The positive electrode active material for an all-solid-state lithium ion secondary battery according to claim 1, wherein the lithium transition metal composite oxide has a compound containing tungsten present between primary particles inside the secondary particles.
4. The positive electrode active material for an all-solid-state lithium ion secondary battery according to claim 1 or 2, wherein the coverage P is 60% or more and 95% or less.
5. The positive electrode active material for an all-solid-state lithium ion secondary battery according to claim 1 or 2, wherein the coverage P is 80% or more and 95% or less.
6. 3. The positive electrode active material for an all-solid-state lithium ion secondary battery according to claim 1, wherein the lithium transition metal composite oxide has a volume average particle diameter Mv of 1 μm or more and 10 μm or less.
7. 3. The positive electrode active material for an all-solid-state lithium ion secondary battery according to claim 1, wherein the content of tungsten contained in the positive electrode active material is 0.1 mass % or more and 6 mass % or less with respect to a total amount of the positive electrode active material.
8. The pore volume of the positive electrode active material is 0.001 cm 3 / g or more 0.008cm 3 3. The positive electrode active material for an all-solid-state lithium ion secondary battery according to claim 1, wherein the average pore size of the positive electrode active material is 1 nm or more and 10 nm or less.
9. 3. An all-solid-state lithium ion secondary battery comprising: a positive electrode containing the positive electrode active material for an all-solid-state lithium ion secondary battery according to claim 1; a negative electrode; and a solid electrolyte.
Citation Information
Patent Citations
Sulfide solid electrolyte
JP2014056661A
All-solid lithium battery
WO2007004590A1